2011
DOI: 10.1002/term.359
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of platelet-rich plasma and fetal calf serum on bone marrow-derived human mesenchymal stromal cells expanded in vitro

Abstract: Mesenchymal stromal cells (MSCs) derived from various sources have great potential for use in cell-based therapies. Since the proportion of primary MSCs contained in bone marrow or adipose tissue is low, plastic adherence and in vitro expansion are necessary to expand MSCs prior to clinical application. Human platelet-rich plasma has been introduced as an alternative serum source but functional differences have so far not been described. Here we cultured MSCs derived from human bone marrow in medium supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 26 publications
2
36
1
1
Order By: Relevance
“…PRP (5% or 10%)-supplemented media heat-inactivated (platelet concentration 79.6 x 10 4 /µL) provided similar results for adipogenic and osteogenic differentiation when compared to 10% FBS (92). Besides, PRP supplemented αMEM also provides osteogenenic, chondrogenic and adipogenic differentiation promoting an increase of cell culture (96)(97)(98)(99)(100)(101)(102).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…PRP (5% or 10%)-supplemented media heat-inactivated (platelet concentration 79.6 x 10 4 /µL) provided similar results for adipogenic and osteogenic differentiation when compared to 10% FBS (92). Besides, PRP supplemented αMEM also provides osteogenenic, chondrogenic and adipogenic differentiation promoting an increase of cell culture (96)(97)(98)(99)(100)(101)(102).…”
Section: Resultsmentioning
confidence: 80%
“…An ASC genome gene expression analysis depicted 102 genes were commonly expressed in differentiated ASC being 90 genes, including those responsible for MSC adhesion, high expressed in 10% FBS-supplemented ASC (24), which may be connected to high sensitivity presented to trypsin by MSC expanded in VBD. Changes in surface markers expression has been contradictorily reported in VBD-expanded MSC (25,49,50,92). HS and aPRP provided maintenance of MSC immunophenotype (25).…”
Section: Discussionmentioning
confidence: 96%
“…In a previous study, CD73 and CD105 were present and CD34 was absent [Baptista et al, 2009]. Therefore, all AT-MSCs expressed CD13, CD73, CD90, and CD105 but did not express hematopoietic markers [Jurgens et al, 2008;Bieback et al, 2009;Griesche et al, 2010;Goedecke et al, 2011]. Adipose tissue SVF contains hematopoietic cells [Varma et al, 2007;Faustini et al, 2010], but these cells are eliminated upon subculture (typically, by passage 3).…”
Section: Discussionmentioning
confidence: 99%
“…MSC migration is investigated in few studies 11,29,32,38 all but one showed enhanced MSC migration in PRP comparing to FBS 29,32 . Moreover, Murphy 32 et al have compared ucPRP (umbilical cord PRP), aPRP (adult PRP), aPPP and FBS effect in MSC migration and found that all forms of human plasma were much more effective in promoting cell migration than FBS.…”
Section: Msc Migrationmentioning
confidence: 99%